Faktor-Faktor yang Mempengaruhi Kepatuhan Individu dalam Membayar Pajak pada Kantor Pelayanan Pajak Pratama Banda Aceh - Maulida Maulida; Mirna Indriani (Program Magister Akuntansi Unsyiah, 2016)
This study aims to examine the factors that influence individual compliance in paying taxes on the Tax Office Pratama Banda Aceh either simultaneously or partially. The population in this study are 100 respondents who are registered taxpayers on the Tax Office Pratama of Banda Aceh. Source data used are primary data through questionnaires delivered directly. Data analysis method used is multiple linear regression analysis. The results showed that the awareness of taxpayers, dissemination of taxation, tax knowledge and modernization of the tax administration system affect the individual compliance in paying taxes on the Tax Office Pratama Banda Aceh either simultaneously or partially. Thus, all the results of this study support the hypothesis.KEYWORDS : awareness of taxpayers, dissemination of taxation, tax knowledge, the modernization of the tax administration system and individual compliance in paying taxes.